World authorship - Boes, Tobias, 1976-; Braun, Rebecca; Spiers, Emily, 1977- (Oxford twenty-first century approaches to literature., 2020)
The original essays in Oxford Twenty-First Century Approaches to Literature mean to provoke rather than reassure, to challenge rather than codify. Instead of summarizing existing knowledge, scholars working in the field aim at opening fresh discussion; instead of emphasizing settled consensus they direct their readers to areas of enlivened and unresolved debate.0Booksellers, authors, and academics have been talking about world literature since Goethe made the term fashionable in the early nineteenth century. Yet amidst all the talk of books that 'circulate' and literature as a kind of universal property that can function as a 'window on the world', how do we account for the people who live in real places, and who write, translate, market, and read the texts that travel on these global journeys? World Authorship breaks new ground by showing how0to bring together the real-world contexts of authorship with the literary worlds of fiction.0Written by world-leading academics and creative professionals including authors, translators, publishers, editors, prize jurors, and literary festival organizers, World Authorship updates Michael Foucault's 'author function' by significantly expanding the network of people and practices involved in literature. It covers keyword aspects of world authorship, grounding them in the study of actual literary texts to illuminate how literature is shared and made in different parts of the world and at different times in history. At the heart of all contributions, however, is one key question: where is the human element in world literature? By covering everything from 'Beginnings' to 'Voice', World Authorship provides the answer.